2006
DOI: 10.1074/jbc.m512529200
|View full text |Cite
|
Sign up to set email alerts
|

Significant Redox Insensitivity of the Functions of the SARS-CoV Spike Glycoprotein

Abstract: The capacity of the surface glycoproteins of enveloped viruses to mediate virus/cell binding and membrane fusion requires a proper thiol/disulfide balance. Chemical manipulation of their redox state using reducing agents or free sulfhydryl reagents affects virus/cell interaction. Conversely, natural thiol/disulfide rearrangements often occur during the cell interaction to trigger fusogenicity, hence the virus entry. We examined the relationship between the redox state of the 20 cysteine residues of the SARS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 36 publications
1
65
0
Order By: Relevance
“…In support of this hypothesis, incubation with iodoacetamide following DTT treatment to prevent reoxidation prevented the recovery of infection following dilution. We also examined whether disulfide reshuffling occurs during entry; 5,5Ј-dithiobis(2-nitrobenzoic acid) (DTNB) concentrations (1-2 mM) used to block free thiols on protein (22,23,33), hence the activity of oxidoreductases, had no effect (Fig. 5), suggesting that free sulfhydryls and redox isomerases are not involved during cell entry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In support of this hypothesis, incubation with iodoacetamide following DTT treatment to prevent reoxidation prevented the recovery of infection following dilution. We also examined whether disulfide reshuffling occurs during entry; 5,5Ј-dithiobis(2-nitrobenzoic acid) (DTNB) concentrations (1-2 mM) used to block free thiols on protein (22,23,33), hence the activity of oxidoreductases, had no effect (Fig. 5), suggesting that free sulfhydryls and redox isomerases are not involved during cell entry.…”
Section: Resultsmentioning
confidence: 99%
“…We confirmed inhibition of infection by Bafilomycin A1, which could not be rescued by pH 3-7 (34), and also found that Bafilomycin A1 treatment and virus binding at 4°C followed by mild reduction (0.04 -0.2 mM) at 37°C and acidic pH levels did not improve infection (not shown). Controls were performed; preincubation of MLVpps (33) with DTNB or DTT prevented infection in a parallel assay, as expected of the inhibition of the redox activity of the envelope endogenous CXXC motif and the reported dependence of MLV entry on the integrity of the envelope redox state (32,33). RSD within each condition was Յ8 and 6% for HCVpps and MLVpps, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the crystal structure, the C480 and C488 of the RBD are crosslinked via a disulfide bond that reduces the flexibility of the L 67 region, limiting its access to the ACE2. On the other hand, it has been reported that the binding of SARS-RBD to ACE2 is insensitive to the redox states of the cysteines to a high extend 26 . Based on the simulation results, we hypothesize that the reduced form of C480 and C488 can also exist during the virus invasion to host cells, and the reduced cysteines can potentially enhance the binding to ACE2.…”
Section: The Conformational Changes Of the Ace2 And The Cov2-rbdmentioning
confidence: 99%
“…In the model of coronavirus spike protein-mediated fusion, receptor binding triggers conformational changes including disulfide reshuffling (Gallagher, 1996;Lavillette et al, 2006) that release HR1 and HR2 to form the coiled-coil fusion motor structure, thereby driving fusion of the viral and host cell membranes and release of the viral ribonucleoprotein into the cytosol (Bosch et al, 2003). The fusion motor complex of S2 consisting of two hydrophobic amino acid 4-3 heptad repeat regions (HR1 and HR2) which form amphipathic helices of a coiled-coil structure has also been solved in several forms (Bosch et al, 2003;Duquerroy et al, 2005;Liu et al, 2004;Tripet et al, 2004;Xu et al, 2004a,b).…”
Section: Spike Proteinmentioning
confidence: 99%